2020
DOI: 10.1021/acs.est.0c01667
|View full text |Cite
|
Sign up to set email alerts
|

Underestimated Sink of Atmospheric Mercury in a Deglaciated Forest Chronosequence

Abstract: Mercury (Hg) deposition through litterfall has been regarded as the main input of gaseous elemental mercury (Hg0) into forest ecosystems. We hypothesize that earlier studies largely underestimated this sink because the contribution of Hg0 uptake by moss and the downward transport to wood and throughfall is overlooked. To test the hypothesis, we investigated the Hg fluxes contributed via litterfall and throughfall, Hg pool sizes in moss covers and woody biomass as well as their isotopic signatures in a glacier-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
147
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(158 citation statements)
references
References 66 publications
10
147
1
Order By: Relevance
“…Using net daily CO 2 uptake to delineate periods of active vegetation growing periods (i.e., June 1 to October 1), the cumulative growing season dry deposition GEM sink amounted to 21.9 μg • m −2 (range of 20.9 to 23.1 μg • m −2 ) (Tables 1 and 2), which is 2.7-fold the value of litterfall mercury deposition, providing evidence that forest-level GEM uptake strongly exceeds litterfall deposition. This finding supports previous reports that large additional deposition fluxes in addition to foliar litterfall and wet deposition are needed to explain observed mercury accumulation in soils along a glacier retreat chronosequence (38).…”
Section: Hour Of Daysupporting
confidence: 92%
See 1 more Smart Citation
“…Using net daily CO 2 uptake to delineate periods of active vegetation growing periods (i.e., June 1 to October 1), the cumulative growing season dry deposition GEM sink amounted to 21.9 μg • m −2 (range of 20.9 to 23.1 μg • m −2 ) (Tables 1 and 2), which is 2.7-fold the value of litterfall mercury deposition, providing evidence that forest-level GEM uptake strongly exceeds litterfall deposition. This finding supports previous reports that large additional deposition fluxes in addition to foliar litterfall and wet deposition are needed to explain observed mercury accumulation in soils along a glacier retreat chronosequence (38).…”
Section: Hour Of Daysupporting
confidence: 92%
“…The forest GEM deposition sink at Harvard Forest may be enhanced by ongoing biomass growth and carbon sequestration driven by forest regrowth, climate warming, and increasing wetting and atmospheric CO 2 concentrations (16). Additional pathways of atmospheric GEM deposition include wash-off of GEM from plant surfaces and deposition via throughfall and stemflow deposition (38). A potentially larger and unaccounted for forest GEM sink will require major revision of other global pool sizes, atmospheric deposition and emission fluxes, and respective residence times in these environmental compartments.…”
Section: Hour Of Daymentioning
confidence: 99%
“…Recent stable Hg isotope studies have shown contrasting results on Hg origins in roots. While one study on rice plants grown in contaminated soils showed root Hg with the same isotopic signature as the surrounding soil 113 , a recent forest study suggested substantial foliage-to-root Hg transport whereby atmospheric Hg(0) uptake via foliage accounted for 44−83% of Hg in tree roots 114 . In the latter study, large roots showed higher proportions of atmospheric Hg(0) and lower soil Hg uptake compared to small roots 114 , possibly related to lower surface areas and reduced absorptive potential of large roots 111,115 .…”
Section: Mercury In Vascular Plants and Mechanism Of Hg Uptakementioning
confidence: 98%
“…Atmospheric Hg(0) taken up by vegetation is oxidized to Hg(II) within the plant tissue (Manceau et al, 2018) and transferred to soils via litterfall (Iverfeldt, 1991;Schwesig and Matzner, 2000;Rea et al, 2001;Graydon et al, 2008;Risch et al, 2012;Jiskra et al, 2015;Wright et al, 2016;Wang et al, 2016;Risch et al, 2017). Moreover, in forests, Hg deposition to the ground may occur by wash-off of Hg(0) from plant surfaces via throughfall and by Hg(0) uptake into woody tissues, lichen, mosses and soil litter (Wang et al, 2020;Obrist et al, 2021). Mercury sequestered by forest ecosystems accumulates in soil and may subsequently be transported from watersheds to streams, rivers and the ocean, where it can bioaccumulate in fish (Drenner et al, 2013;Jiskra et al, 2017;Sonke et al, 2018).…”
Section: Introductionmentioning
confidence: 99%